Investigating target versus impactor influences on Martian crater morphology at the simple‐complex transition. (11th May 2017) - Herrick, Robert R.; Hynek, Brian M.
Abstract: Comparing craters of identical diameter on a planet is an empirical method of studying the effects of different target and impactor properties while holding total impact energy nearly constant. We have analyzed the Martian crater population within a narrow diameter range (7 km < crater diameter < 9 km) at the simple‐complex crater transition using three approaches. We looked for correlations of morphology with surface geology using a global crater database and global geologic map. We examined selected regions in detail with high‐resolution images to further understand the relationship between crater morphology and bulk target properties. Finally, we examined craters in close proximity to each other in order to hold target properties constant, so that we could isolate impactor effects on crater morphology. We found a strong correlation between target properties and interior crater morphology, and we found little evidence that impactor properties (other than impact angle) affect crater appearance. Central uplift and wall slumping are enhanced for less consolidated targets. Layered targets affected both the excavation and modification stages of complex crater formation; the resulting craters have pseudoterraces, flat floors, and central pits.